Enhancing self-regulation as a strategy for obesity prevention in Head Start preschoolers: the growing healthy study - Miller Alison L; Horodynski Mildred A; Herb Holly E; Peterson Karen E; Contreras Dawn; Kaciroti Niko; Staples-Watson Julie; Lumeng Julie C (BMC, 2012)
Abstract Background Nearly one in five 4-year-old children in the United States are obese, with low-income children almost twice as likely to be obese as their middle/upper-income peers. Few obesity prevention programs for low-income preschoolers and their parents have been rigorously tested, and effects are modest. We are testing a novel obesity prevention program for low-income preschoolers built on the premise that children who are better able to self-regulate in the face of psychosocial stressors may be less likely to eat impulsively in response to stress. Enhancing behavioral self-regulation skills in low-income children may be a unique and important intervention approach to prevent childhood obesity. Methods/design The Growing Healthy study is a randomized controlled trial evaluating two obesity prevention interventions in 600 low-income preschoolers attending Head Start, a federally-funded preschool program for low-income children. Interventions are delivered by community-based, nutrition-education staff partnering with Head Start. The first intervention (n = 200), Preschool Obesity Prevention Series (POPS), addresses evidence-based obesity prevention behaviors for preschool-aged children and their parents. The second intervention (n = 200) comprises POPS in combination with the Incredible Years Series (IYS), an evidence-based approach to improving self-regulation among preschool-aged children. The comparison condition (n = 200) is Usual Head Start Exposure. We hypothesize that POPS will yield positive effects compared to Usual Head Start, and that the combined intervention (POPS + IYS) addressing behaviors well-known to be associated with obesity risk, as well as self-regulatory capacity, will be most effective in preventing excessive increases in child adiposity indices (body mass index, skinfold thickness). We will evaluate additional child outcomes using parent and teacher reports and direct assessments of food-related self-regulation. We will also gather process data on intervention implementation, including fidelity, attendance, engagement, and satisfaction. Discussion The Growing Healthy study will shed light on associations between self-regulation skills and obesity risk in low-income preschoolers. If the project is effective in preventing obesity, results can also provide critical insights into how best to deliver obesity prevention programming to parents and children in a community-based setting like Head Start in order to promote better health among at-risk children. Trial registration number Clinicaltrials.gov Identifier: NCT01398358